2021
DOI: 10.1111/imj.15392
|View full text |Cite
|
Sign up to set email alerts
|

Management of diabetes‐related foot disease in the outpatient setting during the COVID‐19 pandemic

Abstract: The use of telephone and/or video consultation in routine management of acute diabetes-related foot disease (DFD) before the coronavirus disease 2019 (COVID-19) pandemic at a tertiary hospital is unprecedented. In March 2020, the Diabetes Feet Australia (DFA) released a national guideline to inform DFD management during the COVID-19 pandemic. The present study aimed to describe the adherence to the DFA guideline of managing acute DFD using telephone and/or video consultation at a Western Australian tertiary ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…The other four studies were undertaken in Qatar, Australia, Colombia and China14,15,19,22. Eight studies looked at data collected during the early period of the COVID-19 pandemic (between March 2020 to September 2020) 12 , 15 , 16 , 17 , 20 , 21 , 22 , 23 , one study looked at data collected between April and June 2021 19 , and two studies looked at data collected throughout the pandemic 14 , 18 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The other four studies were undertaken in Qatar, Australia, Colombia and China14,15,19,22. Eight studies looked at data collected during the early period of the COVID-19 pandemic (between March 2020 to September 2020) 12 , 15 , 16 , 17 , 20 , 21 , 22 , 23 , one study looked at data collected between April and June 2021 19 , and two studies looked at data collected throughout the pandemic 14 , 18 .…”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported the usage of telemedicine during the pandemic, ranging from 12.6-61% of all outpatient appointment encounters during the study period 12 , 14 , 15 , 19 , 23 . Four studies looked at usage during the early part of the pandemic (all during 2020) 12 , 14 , 15 , 23 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be linked to studies showing increased mortality among telehealth services recipients[ 19 ]. It seems that remote DF care during the COVID-19 pandemic became more effective than before, as shown in a study done in Australia examining the adherence to national DF guidelines and treatment efficacy using telemedicine[ 25 ]. This can be attributed to the accumulated knowledge that helped physicians to avoid mistakes of the past, to the increased familiarization of physicians, patients and caregivers with telehealth during the last two years and to the relatively short - term monitoring time of the studies in comparison with previous research.…”
Section: Discussionmentioning
confidence: 99%